Collateral Damage: Low-Income Borrowers Depend on Income-Based Lending - Garmaise, Mark; Jansen, Mark; Winegar, Adam (Journal of Financial and Quantitative Analysis, 2025)
Abstract We use negative durability shocks from vehicle discontinuations to study asset-backed lending and income-based lending (IBL) in auto finance. Discontinuations lead to increased down payments, higher loan-to-value ratios, and larger post-default personal recoveries. These results all indicate that economically disadvantaged consumers are relatively more reliant on unsecured IBL, in stark contrast to corporate financing patterns. Vehicle recoveries on discontinued cars are lower for borrowers who purchase after discontinuations, implying that depreciation is partially borrower-dependent. Our findings suggest that lower-income borrowers, in particular, benefit from technologies that facilitate IBL, such as income monitoring.